1996
DOI: 10.1097/00003246-199602000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of lung function after intratracheal perfluorocarbon administration in healthy animals

Abstract: These findings suggest that partial liquid ventilation with perfluorocarbons lowers pulmonary gas exchange in healthy animals, and the increased pulmonary clearance of 99mTc-DTPA after 3 hrs of this type of ventilatory support may reflect minimal reversible changes in the lung surfactant system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(17 citation statements)
references
References 33 publications
2
15
0
Order By: Relevance
“…The addition of PFC to UW solution for cold preservation of organs before transplantation has been proposed for several years (3)(4)(5)(6)(7)(8)(9)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). PFCs have an innate ability for the maintenance of high-oxygen partial pressures for extended periods of time and the ability to offload oxygen to areas of lower-oxygen partial pressure.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of PFC to UW solution for cold preservation of organs before transplantation has been proposed for several years (3)(4)(5)(6)(7)(8)(9)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). PFCs have an innate ability for the maintenance of high-oxygen partial pressures for extended periods of time and the ability to offload oxygen to areas of lower-oxygen partial pressure.…”
Section: Discussionmentioning
confidence: 99%
“…It is reasonable to speculate that the decrease in compliance with time in these normal lungs may be associated with the introduction of an additional source of interfacial tension at the alveolar surface of the normal lung, as suggested by studies of neonatal lambs 26 (i.e., PFC and lung surface and/or surfactant interface), or it may reflect reversible changes in the alveolar-capillary barrier and surfactant system of the normal lung, as suggested by studies performed in normal rabbits. 27 It is also possible that the trend towards a greater decrease in compliance in the single as compared to multiple dose group by 4 h may be related to redistribution of inspired gas to the nondependent regions, with potential gradual overdistension of the primarily gasfilled regions. Multiple dosing may have more effectively maintained overall lung volume which could serve to counter the negative influence of the additional interfacial tension on compliance.…”
Section: Discussionmentioning
confidence: 99%
“…35 Pulmonary clearance of inhaled technetium-labeled diethylenetriamine pentaacetic acid occurred significantly faster in animals treated with PLV than in animals treated with conventional ventilation alone. The authors concluded that the faster clearance reflected greater alveolocapillary permeability associated with reversible changes in the surfactant system of healthy animals treated with PLV.…”
Section: 12mentioning
confidence: 94%